2007
DOI: 10.1007/s10681-006-9329-7
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mapping of genes determining hairy leaf character in common wheat with respect to other species of the Triticeae

Abstract: Two major genes controlling leaf pubescence were mapped on chromosomes 4BL (Hl1) and 7BS (Hl2 Aesp ) in wheat (Saratovskaya 29) and a wheat/Aegilops introgression line (102/ 00 I ), respectively, together with quantitative trait loci (QTLs) determining hairiness of the leaf margin (QHl.ipk-4B, QHl.ipk-4D) and auricle (QPa.ipk-4B, QPa.ipk-4D) on the long arms of chromosomes 4B and 4D, respectively. The QTLs on chromosome 4D were contributed by a synthetic wheat and, therefore, originated from Aegilops tauschii.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 26 publications
1
33
0
1
Order By: Relevance
“…It is probable that the pubescence locus we found is allelic to, or the same as the hairy leaf gene Hl1 previously reported by Dobrovolskaya et al (2007) in chromosome 4BL of Triticum dicoccoides L. However further evaluations are required to fully determine if this locus is the same as the one we found in Triticum dicoccum Schrank.…”
Section: Discussionsupporting
confidence: 74%
“…It is probable that the pubescence locus we found is allelic to, or the same as the hairy leaf gene Hl1 previously reported by Dobrovolskaya et al (2007) in chromosome 4BL of Triticum dicoccoides L. However further evaluations are required to fully determine if this locus is the same as the one we found in Triticum dicoccum Schrank.…”
Section: Discussionsupporting
confidence: 74%
“…S29 carries two genes for leaf pubescence (Doroshkov et al 2011). One of them, Hl1, was localized and mapped to chromosome 4B (Maystrenko 1976;Dobrovolskaya et al 2007); chromosome location of the second gene is still unknown. Here, we temporarily designat it as Hl3.…”
Section: Development Of Isogenic Linesmentioning
confidence: 99%
“…Some, but not all, are secretory (Solereder 1908), while others act to give protection against both biotic and abiotic factors (Johnson 1975;Valverde et al 2001). It has been shown that leaf trichomes taking part in preserving the photochemistry apparatus (Galmés et al 2007) affect drought tolerance, apparently by limiting transpiration (Barnabás et al 2008). Using the isogenic lines of spring wheat cv.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These transcription factors are transferred from the pubescence to the neighboring cells and compete for binding sites with GL1 and GL3, preventing pubescence growth. Wheat genes Hl2 and Hl2Aesp control pubescence growth and are located on chromosomes 4BL and 7BS [19]. A set of GLOSSY genes in corn has been cloned, which affects pubescence growth as well as morphology and is related to cuticular wax synthesis.…”
mentioning
confidence: 99%